AMF Inoculation Can Enhance Yield of Transgenic Bt Maize and Its Control Efficiency Against Mythimna separata Especially Under Elevated CO2 - Wang, Long; Wang, Xiaohui; Gao, Fanqi; Lv, Changning; Li, Likun; Han, Tong; Chen, Fajun (Frontiers in Plant Science, 2021)
The promotion and application of transgenic Bt crops (Bt crops) provides a new approach for the prevention and control of target lepidopteran pests, and effectively relieves the environmental pressure resulted by the massive usage of chemical pesticides in fields. However, studies have showed that Bt crops will face a new ecological risk of the general decrease in exogenous toxin content grown under elevated carbon dioxide concentration (eCO2), thus negatively affecting the ecological sustainability of Bt crops. Arbuscular mycorrhizal fungi (AMF) are important beneficial microorganism that can effectively improve the nutrient status of host plants, and is expected to relieve the ecological risk of Bt crops especially under global climate change. In this study, the Bt maize (serial number: IE09S034, exogenous gene: Cry1Ie) and its parental line of non-transgenic Bt maize were selected and inoculated with a species of AMF (Glomus caledonium), in order to study the maize secondary defensive chemicals and maize yields, simultaneously to explore the indirect effects of G. caledonium inoculation on the growth, development and reproduction of Mythimna separata fed on Bt mazie and non-Bt maize under aCO2 and eCO2. The results indicated that eCO2 increased the AMF colonization, maize yields and the foliar contents of jasmonic acid (JA) and salicylic acid (SA), but decreased foliar Bt toxin content and Bt gene expression in Bt mazie leaves. G. caledonium inoculation increased maize yields, foliar JA, SA contents, Bt toxin contents and Bt gene expression in Bt maize leaves, and positively improved the growth, development, reproduction and food utilization of the M. separata fed on non-Bt maize. However, G. caledonium inoculation was unfavorable for the fitness of M. separata fed on Bt maize, and the effect was intensified when combined with eCO2. It is presumed that G. caledonium inoculation had adverse effects on the production of non-Bt maize due to the high potential risk of population occurrence of M. separata, while it was just the opposite for Bt maize. Hence, G. caledonium inoculation was conducive to improving the performance of Bt maize for the M. separata control, combined with the better insect resistance under eCO2.